Antibacterial and hemostatic bilayered electrospun nanofibrous wound dressings based on quaternized silicone and quaternized chitosan for wound healing. (5th October 2021) - Gao, Zhongfei; Su, Changming; Wang, Chen; Zhang, Yulong; Wang, Chunhua; Yan, Huanhuan; Hou, Guige
Graphical abstract: Highlights: Cationic silicone derivative QS14 was successfully synthesized and characterized. The bilayered electrospun nanofibrous wound dressing PQCQS consisting of the outer layer PQS and the inner layer PCQC was prepared by electrospinning. PQCQS exhibited the excellent physicochemical properties and good biocompatibility. PQCQS could play a significant role of wound healing in the full-thickness skin defect rabbit ear model. Abstract: The design of novel wound dressings with favorable mechanical properties, hemostasis, inherent antibacterial function, and biocompatibility to facilitate skin wound healing and inhibit scar formation has practical significance in clinical applications. Herein, a bilayered nanofibrous membrane (PQCQS) was fabricated by electrospinning poly(ε-caprolactone) (PCL)/quaternized silicone (PQS, outer layer) and polyvinyl alcohol/collagen/quaternized chitosan (PCQC, inner layer) as wound dressings for damaged skin. The PQS nanofiber was utilized as the outer layer of the wound dressing because it combined the good mechanical property of PCL and antibacterial performance of quaternized silicone to suppress scar formation and provide a stable microenvironment for the wound healing process. The inner membrane (PCQC) exhibited hydrophilicity, biocompatibility, and hemostasis, thus facilitating wound healing. The PQCQS membranes exhibited excellent hydrophilicity, outstanding thermal stability, comparable mechanical properties with human skin, efficient hemostatic performance, and cytocompatibility. Moreover, the PQCQS membranes demonstrated a good balance between antibacterial activity and cell proliferation. Moreover, the PQCQS membranes significantly expedited the wound healing process and inhibited scar hyperplasia better than commercial ointment (MSSG and KELO-COTE) in a rabbit ear full-thickness wounds defect model. That is, the bilayered nanofibrous membranes, with excellent antibacterial activity, hydrophilicity, hemostatic performance, scar inhibition, and wound healing properties, are appropriate candidates for wound dressings.